Draft Genome Sequence of Streptomyces phaeoluteigriseus DSM41896 - Schniete, Jana K. (Genome Announc, 2017)
The draft genome for the type strain Streptomyces phaeoluteigriseus DSM41896 (ISP 5182) is reported. It was classified as a member of the Streptomyces violaceusniger clade; however, a polyphasic study showed it was a separate species based on its distinct spore morphology and 16S rRNA sequence. The genome sequence confirms it as a separate species.